2018
DOI: 10.3390/v10070378
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Felis catus Gammaherpesvirus 1 in Tsushima Leopard Cats (Prionailurus bengalensis euptilurus) on Tsushima Island, Japan

Abstract: Felis catus gammaherpesvirus 1 (FcaGHV1) is a widely endemic infection of domestic cats. Current epidemiological data identify domestic cats as the sole natural host for FcaGHV1. The Tsushima leopard cat (TLC; Prionailurus bengalensis euptilurus) is a critically endangered species that lives only on Tsushima Island, Nagasaki, Japan. Nested PCR was used to test the blood or spleen of 89 TLCs for FcaGHV1 DNA; three (3.37%; 95% CI, 0.70–9.54) were positive. For TLC management purposes, we also screened domestic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Bobcats are presumed to be the primary host species for this virus based on the high prevalence of LruGHV1 DNA in blood and spleen samples from bobcat populations in California, Colorado, Florida, and Vermont (ranging from 25% to 76% positive) (Loisel et al, 2018;Troyer et al, 2014). These findings as well as the recent finding that FcaGHV1 of domestic cats can infect Tsushima leopard cats in Japan (Makundi et al, 2018) further support the idea that felid percaviruses may naturally cross-infect multiple felid species through interspecific felid species interactions.…”
Section: Discussionsupporting
confidence: 56%
“…Bobcats are presumed to be the primary host species for this virus based on the high prevalence of LruGHV1 DNA in blood and spleen samples from bobcat populations in California, Colorado, Florida, and Vermont (ranging from 25% to 76% positive) (Loisel et al, 2018;Troyer et al, 2014). These findings as well as the recent finding that FcaGHV1 of domestic cats can infect Tsushima leopard cats in Japan (Makundi et al, 2018) further support the idea that felid percaviruses may naturally cross-infect multiple felid species through interspecific felid species interactions.…”
Section: Discussionsupporting
confidence: 56%
“…The main mating season in badgers coincides with the postpartum oestrus (in the UK and Ireland typically in the middle of February: [ 37 , 65 ], but males start their “rutting behaviour” several weeks earlier from the middle of January [ 66 ], coinciding with a rise in their testosterone levels [ 67 ]. Testosterone, however, acts as an immune-suppressant [ 68 ] and may thus be partly responsible for the corresponding peak in male MusGHV-1 prevalence rates, mirroring results in domestic cats where males also have a higher risk than females to be infected with the feline gammaherpesvirus FcaGHV-1 [ 33 , 69 ], and entire males are at higher risk of infection with FcaGHV-1 than neutered males [ 70 ]. Female badger MusGHV-1 reactivation rates in the genital tract, in contrast, are higher in spring at the end of the main mating season than at its start in January.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these potential impacts on reproduction, herpesvirus reactivation and associated diseases have rarely been investigated in wildlife. In the Carnivora, reported herpesvirus infections belong mostly to the gammaherpesvirinae, and have been documented from casualties [ 26 , 27 ], epidemiological surveys [ 28 , 29 , 30 ], endangered species management [ 31 , 32 , 33 ], or incidentally from studies that were focused on other pathogens [ 31 ]. Here we report for the first time the results of a systematic screening study of wild European badgers ( Meles meles ; henceforth ‘badger’) from populations across the Republic of Ireland, investigating how Mustelid gammaherpesvirus 1 (MusGHV-1) reactivation in genital tracts affects host reproductive performance.…”
Section: Introductionmentioning
confidence: 99%
“…Novel GHVs were identified among Primates, Artiodactyla, Perissodactyla, Carnivora, Scandentia, and Eulipotyphla using PCR with panherpesvirus DNA polymerase gene primers or genus-specific glycoprotein B (gB) gene primers [19]. In 2014, the first gammaherpesvirus (named Felis catus gammaherpesvirus 1, FcaGHV1 [20]) was identified in domestic cats, followed by the identification of novel GHVs in other felids (bobcats, pumas, ocelots, leopard cats) in the USA and Japan [20,21,22]. Since that first identification, different epidemiological studies have shown that FcaGHV1 infection is widely endemic in domestic cats.…”
Section: Introductionmentioning
confidence: 99%